Seletividade Fisiológica de Endossulfam e Deltametrina às Operárias de A. chartifex spiriti For. (Hymenoptera: Formicidae) em Agroecossistema Cacaueiro do Sudeste da Bahia - MAIA, VALTER B.; BUSOLI, ANTONIO C. [UNESP]; DELABIE, JACQUES H.C. (Sociedade Entomológica do Brasil, 2001)
Avaliou-se o efeito dos inseticidas endossulfam e deltametrina sobre a formiga predadora Azteca chartifex spiriti For., em cultivo do cacaueiro no Sudeste da Bahia, conforme padronização da International Organization for Biological and Integrated Control (IOBC), West Palaearctic Regional Section (WPRS), com algumas modificações. Os testes foram: a) contato; b) pulverização direta; c) persistência. Nos testes de contato, operárias foram expostas a um filme fresco e seco dos inseticidas, aplicado sobre cristalizadores. Nos testes de aspersão, as formigas foram diretamente pulverizadas com os agroquímicos às concentrações recomendadas para o controle de tripes e percevejos. Os insetos foram mantidos a 25±2°C, 65±10% UR e fotofase de 12h. A sobrevivência foi avaliada após 24h e a intervalos variáveis de tempo. Nos testes de persistência, as operárias foram confinadas em cristalizadores e expostas ao contato com folhas de cacaueiro tratadas previamente no campo, sob as mesmas condições controladas. Desenvolveram-se experimentos a um, três, seis, 10, 18 e 32 dias após a aplicação (DAA). Deltametrina foi considerado seletivo nos testes de contato e pulverização direta, não sendo necessária a condução dos testes de persistência em folhas para este inseticida. Endossulfam foi altamente tóxico nos testes de contato e pulverização direta, entretanto, apresentou-se levemente persistente no terceiro teste. A análise conjunta dos três tipos de testes sugere que ambos os inseticidas são seletivos para a espécie benéfica, podendo ser recomendadosem Programas de MIP em agroecossistema cacaueiro. A metodologia proposta pela IOBC/WPRS possibilita estabilidade dos resultados, permitindo sua adaptação e utilização para o fim proposto.

The side effects of the insecticides endosulfan and deltamethrin were evaluated on the predator ant Azteca chartifex spiriti For., in cocoa agroecosystem of South-Eastern Bahia, according to standardization of the International Organization for Biological and Integrated Control (IOBC), West Palaearctic Regional Section (WPRS), with some adaptations to the neotropical conditions. The tests were: a) contact, b) direct spray, c) persistence. In contact tests, exposure of workers to fresh and dry films of insecticides were made. In spray tests, ant workers were directly sprayed with the pesticides. In both contact and spray tests, the insects were kept under controlled conditions of temperature (25±2°C), relative humidity (65±10%) and photoperiod (12h), with the survival evaluation taken 24h after and at variable intervals of time. In the semi-field tests, the insects were kept in glass plates and exposed on cocoa leaves, previously sprayed in the field, under the same controlled conditions. Trials were developed at one, three, six, 10, 18 and 32 days after treatment (DAT). Four categories were used to express the results. Deltamethrin was considered selective in contact and spray tests; then no further tests in semi-field were be necessary for this insecticide. Endosulfan in contact and spray tests was highly toxic (Class 4), though, in semi-field test was slightly persistent (Class 2) The agreement of results among the three types of test suggests that the products are selective for beneficial species, and can be recommended in IPM Programs in cocoa agroecosystem. The standard methodology proposed by IOBC/WPRS shows stability of results, allowing adaptation and utilization for this purpose.
Physiological Selectivity of Endosulfan and Deltamethrin to Workers of Azteca chartifex spiriti For. (Hymenoptera: Formicidae) in Cocoa Agroecosystem of South-Eastern Bahia, Brazil
Keywords: Insecta; Toxicology; predatory ant; Biological control; Insecticide; Insecta; Toxicidade; formiga predadora; Controle biológico; inseticida